Constructivist Dynamics in the Israeli-Palestinian Conflict : Analyzing the Roles of Russia, China, and the United States - Scott, Alexandra Zoe; Garlick, Jeremy; Veselá, Zuzana; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2024)
This paper examines the Israeli-Palestinian conflict through the lens of constructivism, focusing on the period from October 7, 2023, to February 15, 2024. Using critical discourse analysis to compare major international leaders—Joe Biden, Vladimir Putin, and Xi Jinping—this paper investigates how their discourse shapes and reflects geopolitical strategies and national interests. The Israeli-Palestinian conflict remains a pivotal issue in international relations, influencing regional stability and global security. The involvement of significant global players such as the United States, Russia, and China underscores the conflict's broad geopolitical implications. Biden's discourse emphasizes the United States' alliance with Israel, sidelining Palestinian perspectives. In contrast, Putin's rhetoric is expected to highlight Russia's opposition to Western and American dominance, reinforcing its aspirations for global recognition. Xi's narrative is projected to advocate for sovereignty and non-interference, portraying China as a neutral mediator. This research provides insights into how political leaders use language to construct narratives, justify policies, and influence international perceptions, thus contributing to the understanding of the interplay between rhetoric and international relations.
Vedoucí práce: Jeremy Alan Garlick
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: international and diplomatic studies [obor dipl. práce]; diplomové práce; master's theses